Non-Alcoholic Fatty Liver Disease in Pregnancy with Estimation of Feto-Maternal Outcome in a Tertiary Hospital in Bangladesh (The Journal of Ad-din Women's Medical College, 2023)
Background: Non-alcoholic Fatty Liver Disease (NAFLD) is a growing public health concern globally. NAFLD has been linked with adverse pregnancy outcome. The prevalence of NAFLD among women in childbearing age is 10%. During pregnancy both physiologic and pathologic fluctuation in estrogen as well as rapid weight gain plays an important role in the development of NAFLD in mother and infant.Objective: To find out clinical and laboratory profile and pregnancy outcome of patients with fatty liver disease.Methods: We conducted this observational study between January through December 2017 in (pro-women, pro-poor) Ad-din Women Medical College Hospital in Maghbazar, Dhaka, Bangladesh. We enrolled 103 pregnant women who signed the consent (verbal) to participate in the study. Demographic and clinical information was collected using a pre-tested questionnaire.Results: Mean age of the patients was 27 years. During first trimester 18 patients were enrolled, 32 in second and 53 in third trimesters. Of 103, 3 (2.91%) patients had known history of fatty liver disease, 11 (10.68%) had hypertension, 11 (10.68%) had Gestational Diabetes Mellitus (GDM) but none had previous history of Diabetes Mellitus (DM). Among all, 8 (7.76%) patients had previous pregnancy related complications and 32 (31%) had foetal complications including still birth, abortion, neonatal death and Intrauterine Device (IUD). Beside, 92 (89.3%) had grade 1, 10 (9.7%) had grade 2 and one (0.97%) patient had grade 3 fatty liver. 35 (32.4%) patients had high Fasting Blood Sugar level and 26 (24.1%) patients had positive Oral Glucose Tolerance Test (OGTT). And, 31% patients had a high cholesterol level, none had abnormal HDL, 5.8% had high LDL and 78.6% had high TG. USG identified 3 patients with abnormal fetal profile and only 2 patients had adverse pregnancy outcome: one IUD and one abortion.Conclusions: Non-alcoholic fatty liver Disease increases the risk of maternal and fetal complications. Pregnant women should regularly screen for fatty liver disease for early detection and intervention.The Journal of Ad-din Women's Medical College; Vol. 10 (1), Jan 2022; p 33-37